Mixing Bismarck and child pension systems: an optimum taxation approach - Robert Fenge; Jakob von Weizsäcker (Center for Economic Studies and ifo Institute (CESifo), 2006)
The labor-leisure distortion of a pay-as-you-go pension system can be reduced through a stronger tax-benefit link or Bismarck pension system. Distortions of the fertility decision can be reduced through the introduction of a stronger child-benefit or child pension system. Within our optimal taxation framework, we find a Corlett-Hague result regarding the optimal mix of the two: if and only if children are more complementary to leisure should the taxbenefit link be given a positive weight at the expense of the child-benefit link. The model also allows us to examine the infertility insurance argument that may justify redistribution from families with children to those without implied by most pension systems. We find that the opposite redistribution, from the childless to those with children, would be efficient if individuals have low risk aversion. Redistribution in favor of the infertile would only be justified when risk aversion is high.
Keywords: H23; H55; J13; J18; 330